2018
DOI: 10.1021/acs.nanolett.8b02317
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nanostructure Activates TrkB Receptor Signaling of Neuronal Cells by Mimicking Brain-Derived Neurotrophic Factor

Abstract: Brain-derived neurotrophic factor (BDNF), a neurotrophin that binds specifically to the tyrosine kinase B (TrkB) receptor, has been shown to promote neuronal differentiation, maturation, and synaptic plasticity in the central nervous system (CNS) during development or after injury and onset of disease. Unfortunately, native BDNF protein-based therapies have had little clinical success due to their suboptimal pharmacological properties. In the past 20 years, BDNF mimetic peptides have been designed with the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 74 publications
1
82
0
Order By: Relevance
“…They have used peptide sequences as well as functionalized monosaccharides , . They found that the functional sequences were more active when co‐assembled into the nanostructures than on their free states, supporting the use of the nanofibers scaffold . The ratio of functionalized PA in the co‐assembly and the linker length between the active group and the structural part of the functional monomer is critical for their bioactivity (Figure b) , …”
Section: Peptide‐based Co‐assembliesmentioning
confidence: 85%
See 1 more Smart Citation
“…They have used peptide sequences as well as functionalized monosaccharides , . They found that the functional sequences were more active when co‐assembled into the nanostructures than on their free states, supporting the use of the nanofibers scaffold . The ratio of functionalized PA in the co‐assembly and the linker length between the active group and the structural part of the functional monomer is critical for their bioactivity (Figure b) , …”
Section: Peptide‐based Co‐assembliesmentioning
confidence: 85%
“…The inclusion of the structural sequence in the active monomers facilitates their incorporation into the nanostructures in a random way that can get disruptive at high percentages of the active monomer if the epitope has a destabilizing effect in the structure . This type of homo‐co‐assemblies has been used to incorporate active sequences to target proteins for neuronal cell maturation,, bone generation, and cartilage regeneration . They have used peptide sequences as well as functionalized monosaccharides , .…”
Section: Peptide‐based Co‐assembliesmentioning
confidence: 99%
“…Phosphorylated and total CREB proteins were decreased in both the cytoplasm and nucleus of Aβ‐treated cells (Rosa & Fahnestock, ). BDNF and its receptor, TrkB, are widely expressed in the brain and participate in a series of intracellular signaling processes, neuronal protection and survival, axonal and dendritic morphology, and synaptic plasticity (Edelbrock, Alvarez, Simkin, & Fyrner, ) The increased phosphorylation of TrkB at Thr515, through which BDNF exerts its neuronal protective functions, consists with increased expression of BDNF. The activated TrkB interacts with and phosphorylates several intracellular targets, including PI3K/Akt, Ras/MAPK/ERK, and CaM signal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersion of hepatocyte‐like spheroids in a RAD16‐I peptide hydrogel showed that the generated 3D hydrogel significantly tailored cellular proliferation and presented matured differentiation profiles . Indeed, it has been recently disclosed that the bioactivity of amphiphile mimetic peptides (e.g., brain‐derived neurotrophic factor, BDNF) can be augmented in 3D hydrogels due to conformationally improved peptide–cell interactions in these systems, which not only encourages cell infiltration but increases functional maturation of the construct . A co‐assembly system of peptide amphiphiles designed to form nanofibers targeting cartilage repair was also proven promising for tissue regeneration based on a cell encapsulation approach .…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%